EXTREME FACTORS IN THE ACTIVITY OF BASKETBALL PLAYERS MODERN CONCEPTION - Т. В. Клюев (Science and Innovation Center Publishing House, 2014)
In extreme competitive situations pedagogical influence of the coach should become the main method of the team managing: couch must activate the behavior of the players, inspire them, define the goal and methods, see the situation evenly and cooperate with the team. Finding the solution to the problem depends on the individual traits of the sportsman and his readiness to extreme situations during the match. Purchase on Elibrary.ru > Buy now